A direct regional scale estimate of transgene movement from genetically modified oilseed rape to its wild progenitors - M. J. Wilkinson; I. J. Davenport; Y. M. Charters; A. E. Jones; J. Allainguillaume; H. T. Butler; D. C. Mason; A. F. Raybould (Molecular Ecology, 2000)
One of the major environmental concerns over genetically modified (GM) crops relates to transgene movement into wild relatives. The pattern of hybridization ultimately affects the scale and rapidity of ecological change and the feasibility of containment. A new procedure for quantifying hybrid formation over large areas is described. Remote sensing was used to identify possible sites of sympatry between Brassica napus and its progenitor species across 15 000 km 2 of south‐east England in 1998. Two sympatric populations with B. rapa and one with B. oleracea were found over the entire survey area. Every newly recruited plant in these populations in 1999 was screened for hybrid status using flow cytometry and molecular analyses. One hybrid was observed from the 505 plants screened in the B. rapa populations but none of the nine B. oleracea recruits were hybrids. Measures to minimize gene flow are suggested, and a procedure for the post‐release evaluation and containment of GM cultivars is proposed.